Study on a Brain-Controlled Pneumatic Actuator to Assist Emergency Braking of a Vehicle - Ryszard Dindorf; Jakub Takosoglu; Piotr Wos (Communications - Scientific letters of the University of Zilina, 2021)
This article deals with the issue of safety within the road freight transport sector with regards to the securing of cargo on a vehicle. The first part of the article focuses on the legal framework that regulates this issue in the Czech Republic. The second part is based on a case study and survey conducted among drivers of the road freight transport vehicles into their awareness of what they understand is meant by securing and secure cargo. The case study was carried out in a specific transport company and includes an analysis of the current situation and concrete measures for improving safety while securing timber for transport.